2020
DOI: 10.1155/2020/1359164
|View full text |Cite
|
Sign up to set email alerts
|

Copper Induces Oxidative Stress and Apoptosis in the Mouse Liver

Abstract: Copper (Cu) is an essential trace element involved in the normal physiological processes of animals. However, excessive exposure to Cu can produce numerous detrimental impacts. The aim of this study was to investigate the effects of Cu on oxidative stress and apoptosis as well as their relationship in the mouse liver. Four-week-old ICR mice (n=240) were randomly assigned to different Cu (Cu2+-CuSO4) treatment groups (0, 4, 8, and 16 mg/kg) for periods of 21 and 42 days. The high doses of Cu exposure could indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 47 publications
2
63
0
1
Order By: Relevance
“…19 Additionally, cleaved PARP can also be upregulated during the cell apoptosis. 20,21 Our finding was consistent with these studies, suggesting that knockdown of MAGOH or double knockdown of MAGOH and MAGOHB induced the apoptosis of gastric cancer cells via upregulation of cleaved caspase 3 and cleaved PARP. Cyclin B1, CDK1 and p27 Kip1 were key mediators in cell cycle distribution.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…19 Additionally, cleaved PARP can also be upregulated during the cell apoptosis. 20,21 Our finding was consistent with these studies, suggesting that knockdown of MAGOH or double knockdown of MAGOH and MAGOHB induced the apoptosis of gastric cancer cells via upregulation of cleaved caspase 3 and cleaved PARP. Cyclin B1, CDK1 and p27 Kip1 were key mediators in cell cycle distribution.…”
Section: Discussionsupporting
confidence: 90%
“…Cells were cultured in RPMI 1640 supplemented with 10% fetal bovine serum (FBS), 100 μg/mL streptomycin and penicillin at 37°C in 5% CO 2 . The use of cells was approved by the Ethics Committee of Zhejiang University School of Medicine (20,190,711).…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Cu overdose could disturb this balance and induce the production of excessive ROS, which leads to lipid, protein and DNA damage ( 39 ). Previous studies demonstrated that CuSO 4 or copper chloride (CuCl 2 ) exposure can induce the production of excessive ROS in HEK293 cells, mouse liver cells or neuronal cells ( 23 , 40 , 41 ). Mitochondria are not only the major producer of cellular ROS but also a target ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…As revealed in previous studies, various death pathways have been triggered upon copper exposure, depending on the copper concentration used, treatment period and the cellular or animal model under study. Copper overload may result in caspase-dependent and caspase-independent programmed cell death, autophagy and necrosis [ 19 , 42 , 43 ]. In some studies, exposure to excess copper initiated a classical apoptotic pathway and the activation of executioner caspase-3 [ 43 ].…”
Section: Discussionmentioning
confidence: 99%